Relationship between thigh muscle cross-sectional areas and single leg stand-up test in Japanese older women - Keiko Kishigami; Hiroaki Kanehisa; Shumeng Qi; Takuma Arimitsu; Motohiko Miyachi; Motoyuki Iemitsu; Kiyoshi Sanada (PLoS ONE, 2022)
In older adults, the quantitative decline of the quadriceps femoris is associated with the augmentation of difficulty in the execution of a stand-up task. However, it is unclear whether the cross-sectional areas (CSAs) of individual thigh muscles differ between older adults who can stand up from a 40-cm-height chair on a single leg and those who cannot. To investigate this, the present study determined the CSAs of individual mid-thigh muscles in 67 Japanese women aged 60–77 years by using a magnetic resonance imaging method. Participants were asked to stand up from a 40-cm-height chair on a single leg, and those who could and could not stand up without leaning back and maintain a standing posture for 3 seconds on a single leg were allocated into the successful group (SG, n = 40) and unsuccessful group (USG, n = 27), respectively. Only the CSA of the adductors (sum of the adductor longus and adductor magnus) was significantly smaller in USG compared to SG. When CSA was expressed relative to the two-third power of body mass, the values for the four heads of the quadriceps femoris and biceps femoris long head, as well as the adductors, were significantly lower in USG than in SG. The current results indicate that in terms of the value relative to body mass, the reduced CSAs of the adductors and biceps femoris long head, as well as the four heads of the quadriceps femoris, are associated with the failure of attempts to stand up from a 40-cm-height chair on a single leg in older women. This may be due to the anatomical function of the two muscle groups, which contributes to hip extension movement involved in transitioning from a sitting position to a standing position during the stand-up task.